2007
DOI: 10.1161/strokeaha.106.474569
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Variables for Mortality After Acute Ischemic Stroke

Abstract: The results indicate that subjects with acute ischemic stroke are at increased risk of all-cause mortality. Advancing age, large-vessel stroke, atrial fibrillation, and previous stroke/transient ischemic attack predict mortality; and analysis of albumin, creatinine, von Willebrand factor, and beta-thromboglobulin will aid in the identification of patients at increased risk of death after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
117
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 29 publications
8
117
1
5
Order By: Relevance
“…Also, the severity of impaired kidney function was associated with increased risk of early mortality (odd ratio= 1.7, 95% CI =1.4-2 , per 1mg/dl increase in serum creatinine). Similarly, Carter et al 33 . showed that serum creatinine level was a strong predictor of mortality in patients with ischemic stroke.…”
mentioning
confidence: 86%
“…Also, the severity of impaired kidney function was associated with increased risk of early mortality (odd ratio= 1.7, 95% CI =1.4-2 , per 1mg/dl increase in serum creatinine). Similarly, Carter et al 33 . showed that serum creatinine level was a strong predictor of mortality in patients with ischemic stroke.…”
mentioning
confidence: 86%
“…Based on publications identified by Miyasaka et al, 89 Carter et al 90 and Pocock et al, 91 people with AF, stroke or HF are assumed to be at increased risk of all-cause mortality versus the UK general population. Furthermore, people with AF and stroke and people with AF and HF are assumed to be at further risk of death as a result of the concomitant conditions.…”
Section: Mortalitymentioning
confidence: 99%
“…Case fatality as a result of stroke was calculated from data presented by Carter et al 90 Carter et al 90 report the number of people dying within 30 days of an acute stroke event (n = 32/545) and, of these, the number with concomitant AF (n = 14). Table 39 summarises the calculation of the probability of stroke case fatality in people with and without AF.…”
Section: Mortalitymentioning
confidence: 99%
“…8) In patients with acute ischemic stroke, a condition resembling acute coronary syndrome, a low serum albumin level was observed in several patients and has been shown to be an independent predictor of mortality in acute ischemic stroke. 10) The aim of the present report was to determine the association between low serum albumin levels measured immediately upon hospital admission and in-hospital adverse outcomes in patients with acute coronary syndrome. Furthermore, we combined this association with other variables to assess the value of albumin in predicting adverse outcomes.…”
mentioning
confidence: 96%